Review : Klasifikasi dan Sifat Mekanis Tanah Asli di Pulau Bintan sebagai Subgrade Perkerasan Jalan - Ferly Oktavia; Dian Kharisma Dewi (Pusat riset dan Inovasi Nasional, 2026)
Bintan Island has abundant bauxite soil resources; however, its utilization as road construction material remains limited. The scarcity of high-quality granular material in the region necessitates the use of available local resources, particularly for pavement subgrade layers. This article aims to analyze the classification and mechanical properties of native soils in Bintan Island through a systematic literature review. The reviewed literature includes laboratory test results of bauxite soil. The findings indicate that bauxite soil exhibits low plasticity, relatively high CBR values (±35%), and is classified as CL (USCS) and A-2-4 (AASHTO). These results suggest that bauxite soil is suitable for subgrade applications, although require stabilization with binding agents. The implication of this review highlights that the utilization of local materials could support sustainable infrastructure development in island regions by reducing dependency on imported materials.